IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KAMPUNG CURUG SAWER PANDEGLANG - Qirana Nabillang; Titi Stiawati (LPPM STIA Banten, 2023)
The purpose of this study was to find out the implementation of the non-cash food assistance program in Curug Sawer Pandeglang village. As for the problem in the study, there were inaccuracies in targeting BPNT recipients, lack of communication between BPNT implementers, uncertain schedules for providing BPNT, no socialization regarding non-cash food assistance in Curug Sawer Pandeglang Village. The research method used by researchers is a qualitative approach. As for the results or findings that the researchers got, the BPNTin Curug Sawer village still needed to be improved both in determining the goals of the program, time resources, the characteristics of implementing agents, and communication between organizations. The suggestions that the researchers that the researchers gave were to improve the existing mechanisme of the BPNT program and improve communication between parties involved in implementing the BPNT program by going directly to the field so that socialization and data collection could be on target.